ANALISIS MANAJEMEN RISIKO PADA INDUSTRI KAFE UNTUK MENINGKATKAN EFISIENSI DI “KAFE MUKA BUMI” - Nazhara Azmi; Rd. Ghina Fithriyah; Syahla Mutia Aini; Asep Suwarna (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Risk management is an important element in managing a cafe business to improve efficiency and ensure operational sustainability. This research aims to analyze risk management at “Muka Bumi Café” with a focus on Operational Risk, Human Resources Risk, Financial Risk, Marketing Risk, and Inherent Risk. This research uses qualitative methods with data collection techniques through interviews, observation, and data analysis. The results showed that Muka Bumi Cafe has implemented a comprehensive risk management strategy, through risk identification, measurement, and control. This research provides a practical contribution for café managers in building resilient risk management.